Enhancing Reading Interest and Comprehension through Literature Circles - Amalia, Dini (JELP Journal of English Language and Pedagogy, 2025)
This paper investigates the impact of utilizing literature circles as an instructional strategy to improve reading interest and comprehension among students. By acknowledging the persistent challenge of cultivating a passion for reading and fostering strong comprehension skills, this study inquires the efficacy of literature circles in creating an interactive and collaborative reading environment. The study aims to provide empirical insights into the tangible benefits of literature circles as a pedagogical tool. The research design employs descriptive quantitative methodologies to analyze the effectiveness of literature circle among students and scrutinize the impact of active engagement in literature circle discussions and subsequent reading comprehension performance. The use of paired t test is crucial to examine the data result. The findings shows that Literature Circle affects students’ interest and comprehension of reading. There are significant scores revealing students’ improvement. By examining reading result through literature circle participation, this research contributes to the field of literacy education, offering evidence-based strategies to enhance students' reading interest, experiences and comprehension abilities. The findings have practical implications for educators seeking innovative and effective approaches to cultivate the interest for reading while ensuring meaningful comprehension gains among students